Experimental study of the use of piritramide as intrathecal analgesic - Tica, V I; Neştianu, V; Tica, A A; Beghim, M; Serbanescu, L; Beghim, Esra; Bafani, S (Chirurgia (Bucharest, Romania : 1990), 2007)
Opioids proved their advantages as general and intrathecal (i.t.) analgesics. Piritramide (P), a largely used analgesic opioid today, has not been studied in i.t. administration. Our experimental research aimed in determining the efficiency, security and optimal dose of i.t. P. In 9 adult mongrel dogs equally randomized in 3 groups we injected i.t. P 1.3 mg x kg-l (group 1), P 0.8 mg x kg-l (group 2) and sodium chloride 0,9% (group 3) and we registered the motility, the pain reaction to electrical and mechanical nociceptive stimuli, the respiratory rate and amplitude, electrocardiogram, heart rate, mean arterial blood pressure electroencephalogram and, for 2 subjects from group 1, electromyogram. The P-induced analgesia was strong, dose-dependent, and segmental, with a time of onset of 5-8 min, duration of 1h 45 min-2h 30 min, and prolonged residual analgesic level for 5-6 h. The dogs from the 1st group presented moderate side effects: bradypnea, tachycardia and arterial hypotension at 5 min, reduction in the posterior limbs motility, sleep. We could conclude that i.t. piritramide 0.8 mg x kg-l provides a solid, segmental, long-lasting analgesia, without marked adverse effects.